1999
DOI: 10.3354/dao038163
|View full text |Cite
|
Sign up to set email alerts
|

Experimental susceptibility of turbot Scophthalmus maximus to viral haemorrhagic septicaemia virus isolated from cultivated turbot

Abstract: Juvenile pathogen-free turbot were infected with a viral haemorrhagic septicaemia virus (VHSV) isolate recovered from turbot cultivated on the island of Gigha, West Scotland. Mortality of 100% was recorded in fish lnfected via the intra-peritonea1 (i.p.) route. Horizontal transmission of VHSV in sea water was demonstrated by cohabitation of naive fish with i.p. infected fish at a ratio of 1:l. The total cumulative average mortality in cohabiting fish was 60% by 60 d post-infection. Turbot infected via an immer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
44
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 9 publications
(11 reference statements)
8
44
0
Order By: Relevance
“…It was previously reported (Castric & Jeffroy, 1991) that isolate L59X is pathogenic by intra-peritoneal injection to sea bass Dicentrarchus labrax, sea bream Sparus aurata and turbot Scophtalmus maximus. These results are in agreement with recent data from Snow & Smail (1999) who showed that a marine isolate of VHSV (860/14) Fig. 3.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It was previously reported (Castric & Jeffroy, 1991) that isolate L59X is pathogenic by intra-peritoneal injection to sea bass Dicentrarchus labrax, sea bream Sparus aurata and turbot Scophtalmus maximus. These results are in agreement with recent data from Snow & Smail (1999) who showed that a marine isolate of VHSV (860/14) Fig. 3.…”
Section: Discussionsupporting
confidence: 83%
“…It was previously reported (Castric & Jeffroy, 1991) that isolate L59X is pathogenic by intra-peritoneal injection to sea bass Dicentrarchus labrax, sea bream Sparus aurata and turbot Scophtalmus maximus. These results are in agreement with recent data from Snow & Smail (1999) who showed that a marine isolate of VHSV (860/ 52: 29-37, 2002 from turbot, which can also be classified within genotype II, is highly pathogenic to turbot under various experimental conditions, including by bath. However, whether L59X could infect turbot by bath exposure is not yet known.…”
supporting
confidence: 83%
“…Atlantic salmon parr (mean weight 27.5 g) and Atlantic salmon post-smolts (mean weight 273 g) were reared at the FRS Marine Research Unit, Aultbea, Ross-shire, Scotland. Before the infection experiments fish were screened for the presence of ISAV, viral haemorrhagic septicaemia virus, infectious haematopoietic necrosis virus and infectious pancreatic necrosis virus by standard virology tissue culture methods as previously described (Dannevig et al 1995, Snow & Smail 1999 and, for ISAV, by reverse transcription polymerase chain reaction (RT-PCR) (Mjaaland et al 1997).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Methods. Cell culture and virus propagation: The epithelioma papulosum cyprini (EPC) cell line (Fijan et al 1983) was used for the isolation, propagation and identification of virus in this study according to previously described methods (Snow & Smail 1999). The isolate of VHSV used in this study was recovered in 1995 from wild cod caught in the North Sea (H16/7/95; Smail 2000).…”
mentioning
confidence: 99%
“…Rainbow trout (mean weight 9.1 g) were produced at the FRS Experimental Fish Production Unit, Aultbea, Wester-Ross, Scotland and used as the reference susceptible fish species (de Kinkelin et al 1979, de Kinkelin & Castric 1982. Prior to infection, 10 fish were sacrificed and the organs (kidney, liver and spleen) of individual fish removed and screened for the presence of VHSV, infectious pancreatic necrosis virus (IPNV) and infectious naematopoietic necrosis virus (IHNV) as previously described (Snow & Smail 1999).…”
mentioning
confidence: 99%